Effect of Infection and Environmental Sanitation on Stunting in Rural Toddlers - Rahardjo, Setiyowati; Erna Kusuma Wati; Aisyah Apriliciciliana Aryani (Department of Nutrition, Faculty of Health Sciences, Universitas Brawijaya Malang, 2025)
The surge in COVID-19 cases among children poses a risk of malnutrition, especially stunting, and even mortality. According to Banyumas Health Data in 2019, the highest prevalence of stunting in rural areas (25.9%) was at the Cilongok I Primary Health Center. Nutritional problems in urban and rural areas are influenced by differences in healthcare facilities and food availability. This study aimed to examine the effect of infection and environmental sanitation on the incidence of stunting among toddlers in rural areas during the COVID-19 pandemic. A case-control approach was used in this study. The case group consisted of stunted toddlers based on Height-for-Age Z-score (HAZ) measurements in February 2021, and the control group was toddlers with normal nutrition who were the closest neighbors of the cases. A total of 30 stunted toddlers and 30 controls were selected using simple random sampling. Data were analyzed using multivariate, bivariate, and univariate analysis with logistic regression. The results showed that infection and environmental sanitation influenced the occurrence of stunting among toddlers in rural areas. Infection was the most dominant factor, with an OR value of 16.34, meaning that infected toddlers faced 16.34 times higher risk of becoming stunted than those without infections.